Evaluación de la calidad de atención desde la percepción de la usuaria de consulta externa de ginecología y obstetricia hospital san juan de dios cara 2008 - Quispe Gómez, Maximiliana (2013)
This study was conducted in the San Juan de Dios Hospital Caraz, with the overall objective of assessing the quality of care in the outpatient Obstetrics and Gynecology Service. The type of study was an observational, with a crossover design, the sample consisted of 205 users: Measurement of quality is done through user satisfaction using SERVQUAL survey. It was found that 92.2%, of users, are among those aged 20-45 years (adult), 36.1% had completed primary education, 93.6% live in the urban area and 61 0% have some type of insurance. Regarding overall satisfaction was found that 94.2% of respondents expressed dissatisfaction, of which 84.9% had mild or moderate and 9.3% dissatisfaction to severe dissatisfaction. The satisfaction of users according to dimensions: Reliability shows the highest degree of dissatisfaction with 83.9%, followed by tangible aspects that rank second in dissatisfaction with 81.4%. Safety 79.5% shows some degree of dissatisfaction, the dimension of the rapid response, 76.1% with some degree of dissatisfaction; Empathy showed less dissatisfaction 68.8% and 31.3% expressed varying degrees of satisfaction. The results show that the perceived quality of care and user outpatient obstetrics gynecology service is inadequate in its entirety. The expectations of the users with respect to components of the dimensions are high.